The Importance of Managing Customer Service, Safety Quality and Benchmarking of Airports and Airlines to Enhance the Performance and Customer Loyalty (Global Journal of Management and Business Research, 2014)
Customer service, safety quality and benchmarking are all important aspect that airports and airlines should take into account. There are several importance, drawbacks and ways to manage each of these components .It has been found that all these three components are interrelated to one another, somehow to promote better performance. This is because with benchmarking, an airport or airline will be able to improve its performance, better performance means more customers, and more customers' means more expectation of good service and proper management of safety. All of these expectations needs to be fulfilled in order for them to feel secure and at the same time would be more willing to come back in the future.
Keywords: customer service; safety quality; bench-marking; airport; airline